Reforma do Ensino Médio: o debate da audiência pública - região Sul - Zago, Mayara Amanda Pratta (2020)
The object of this research is the public hearing on the third version of the National Common Curricular Base - a document whose objective is to guide the school curriculum of basic education - held in Florianópolis, in May 2018. Since 2015, public hearings to discuss this Base were being held in many regions of Brazil. The research objective is aimed at understanding the conflict settled between the positioning of the parts concerning the transformation in the Brazilian educational system, which was established in 2016. The whole year was marked by ruptures and changes, but one, the Reform in High School, among so many, became the subject of debates, protests, and occupations - especially because it was an act enacted by a Provisional Measure. The theoretical perspective used goes through Bourdieu to think about dispositions, disputes, and the role of the school institution, and also Thompson to think about social conflict. To achieve the research objective, it was necessary to transcribe the audience's video for reading and analysis of the participants' positions. There was also a historical retrospective of education in Brazil, and a historical retrospective of the creation of the institutions that participated in the audience. This path made it possible to relate provisions to the content of the debate and to identify aspects of the reform that can be compared to other events in the history of our country. Even though the establishment of the Base may mean the defeat of a significant part of the positions expressed in the debate, the verbalization of divergences, contradictions, and the experience of a democratic space thus constructed are indelibly integrated, through experience, to the construction of identity.